Reconfiguring in-patient services for adults with mental health problems: changing the balance of care. Issue 6 (November 2018) - Tucker, Sue; Hughes, Jane; Jolley, David; Buck, Deborah; Hargreaves, Claire; Challis, David
Abstract : Background: Research suggests that a significant minority of hospital in-patients could be more appropriately supported in the community if enhanced services were available. However, little is known about these individuals or the services they require. Aims: To identify which individuals require what services, at what cost. Method: A 'balance of care' (BoC) study was undertaken in northern England. Drawing on routine electronic data about 315 admissions categorised into patient groups, frontline practitioners identified patients whose needs could be met in alternative settings and specified the services they required, using a modified nominal group approach. Costing employed a public-sector approach. Results: Community care was deemed appropriate for approximately a quarter of admissions including people with mild-moderate depression, an eating disorder or personality disorder, and some people with schizophrenia. Proposed community alternatives drew heavily on carer support services, community mental health teams and consultants, and there was widespread consensus on the need to increase out-of-hours community services. The costs of the proposed community care were relatively modest compared with hospital admission. On average social care costs increased by approximately £60 per week, but total costs fell by £1626 per week. Conclusions: The findings raise strategic issues for both national policymakers and local service planners. Patients who could be managed at home can be characterised by diagnosis. Although potential financial savings were identified, the reported cost differences do not directly equate to cost savings. It is not clear whether in-patient beds could be reduced. However, existing beds could be more efficiently used. Declaration of interest: None.